First-Year Students’ Perceptions of Their Learning Experience at Industrial University of Ho Chi Minh City - Nguyen, Thi Thu Trang; Nguyen, Thi Ngoc Diep; Ly, Thanh Binh; Dao, Thi Nguyet Anh; Pham, Thi Oanh; Do, Thi Thin (Journal of Technical Education Science, 2023)
This study explored how first-year students perceived their learning experience at Industrial University of Ho Chi Minh city (IUH). The freshmen’s learning experience was measured by their academic, social, and emotional involvement in educationally purposeful activities. The research also examined the intercorrelations of various aspects of learning experience and their relationships with freshmen’s satisfaction and sense of belonging. Data collected from an online survey with the participation of 898 IUH first-year students showed that students highly rated the quality of their lecturers’ teaching practices, the institutional support, and expressed their satisfaction with their entire learning experience. Data, however, indicated areas that needed improving. IUH first-year students did not make enough academic effort because of low levels of the coursework’s challenge. Moreover, the quantity and quality of the interactions between first-year students and other members of IUH were still low, which negatively affected students’ sense of belonging to the university. The study also pointed out factors positively correlated with students’ satisfaction and sense of belonging, including the institutional support, the quality of students’ relationships with socializing agents on campus, and the high quality of teaching practices. Based on these results, some suggestions were put forward to help IUH motivate first-year students to make more effort in their study; support and encourage students’ better integration with IUH learning environment; and increase students’ sense of belonging to the university.